The increase in O2 nodule-conductance under phosphorus deficiency varies among genotypes in Medicago truncatula: Nodule respiration stimulated under P. deficiency - Aydi, Samir; Kouas, Saber; Sassi Aydi, Sameh; Rahmani , Rami; Abdelly, Chedly (Cellular and Molecular Biology, 2022)
The effect of phosphorus deficiency on plant growth, nodulation, and symbiotic nitrogen fixation as well as, the nodulated-roots oxygen consumption, nodule permeability and conductance to the oxygen diffusion of Medicago truncatula–Sinorhizobium meliloti symbiosis were studied. Three lines, namely TN6.18, originated from local populations, F83005.5 originated from Var (France) and Jemalong 6, a reference cultivar from Australia, were hydroponically grown in nutrient solution supplied with 5 µmol (P deficient) and 15 µmol (P sufficient: Control), under semi-controlled conditions in a glasshouse. A genotypic variation in tolerance to P deficiency was found: TN6.18 was the most tolerant line whereas F83005.5 was the most sensitive. The relative tolerance of TN6.18 was concomitant with the greater P requirement, the higher N2 fixation, the stimulation of nodule respiration and the less increases of conductance to the oxygen diffusion in nodules tissues. The higher P use efficiency for nodule growth and for symbiotic nitrogen fixation was detected in the tolerant line. Results suggest that the tolerance to P deficiency seems to depend on thehost plant ability to reallocate P from both leaves and roots to their nodules. P is needed in high energy demand conditions to maintain adequate nodule activity and prevent negative effects of the O2 excess on the nitrogenase.